PENGEMBANGAN MEDIA PEMBELAJARAN BAHASA INGGRIS BERBASIS TEKS CERITA UNTUK MENINGKATKAN KEMAMPUAN MENDENGARKAN SISWA MENGGUNAKAN CANVA - sitifadila; Siti Niah; Pahmi (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2026)
This study aimed to develop and evaluate English learning media using the canva application to enhance grade X students' listening skills in recount text material at SMK Muhammadiyah 3 Pekanbaru. The research employed a Research and Development (R&D) approach with the ADDIE model, encompassing Analysis (needs assessment via school observations), Design (storyboarding and flowcharting), Development (content creation and video editing in Canva), Implementation (pre-test, media devilery, and post-test), and Evaluation (expert validations and data analysis). The study involved 32 sample students in November 2023. Quantitative data from expert questionnaires were analyzed using feasibility percentages, while pre-post differences were calculated via the N-gain formula. The Canva-based learning media proved feasible and effective in addressing listening challenges for recount text, significantly improving student comprehension and engagement. This development supports innovative, accessible audiovisual tools for English instruction in resource-limited settings.